2021
DOI: 10.1007/s00330-021-07967-x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of relevant extracardiac findings on coronary computed tomography angiography vs. invasive coronary angiography

Abstract: Objectives To compare the detection of relevant extracardiac findings (ECFs) on coronary computed tomography angiography (CTA) and invasive coronary angiography (ICA) and evaluate the potential clinical benefit of their detection. Methods This is the prespecified subanalysis of ECFs in patients presenting with a clinical indication for ICA based on atypical angina and suspected coronary artery disease (CAD) included in the prospective single-center randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
(39 reference statements)
0
3
0
2
Order By: Relevance
“…In one study on emergency care by Onuma et al, an alternative extracardiac disease was able to be identified as the cause of acute angina pectoris symptoms in 16 % of patients based on cardiac cross-sectional imaging so that further imaging was not necessary [121]. Dewey et al were able to confirm this with 12.9 % detected extracardiac causes for atypical angina pectoris [122]. In a further study by Lehmann et al, extracardiac findings changed management in 1.3 % of patients and provided an alternative explanation for angina pectoris symptoms in 4.1 % of patients [123].…”
Section: Extracardiac Findingsmentioning
confidence: 98%
See 1 more Smart Citation
“…In one study on emergency care by Onuma et al, an alternative extracardiac disease was able to be identified as the cause of acute angina pectoris symptoms in 16 % of patients based on cardiac cross-sectional imaging so that further imaging was not necessary [121]. Dewey et al were able to confirm this with 12.9 % detected extracardiac causes for atypical angina pectoris [122]. In a further study by Lehmann et al, extracardiac findings changed management in 1.3 % of patients and provided an alternative explanation for angina pectoris symptoms in 4.1 % of patients [123].…”
Section: Extracardiac Findingsmentioning
confidence: 98%
“…In einer Studie zur Notfallversorgung von Onuma et al konnte basierend auf der kardialen Schnittbildgebung bei 16 % der Patienten eine alternative, extrakardiale Erkrankung als Ursache einer akuten Angina-pectoris-Symptomatik identifiziert werden, sodass eine weitere bildgebende Diagnostik nicht notwendig war 121 . Dewey et al konnten dies mit 12,9 % detektierter extrakardialer Ursachen für eine atypische Angia pectoris bestätigen 122 . In einer weiteren Studie von Lehmann et al änderten extrakardiale Befunde das Krankenhausmanagement bei 1,3 % der Patienten und lieferten eine alternative Erklärung für eine Angina-pectoris-Symptomatik bei 4,1 % der Patienten 123 .…”
Section: Befundungunclassified
“…Dewey et al. konnten dies mit 12,9 % detektierter extrakardialer Ursachen für eine atypische Angina pectoris bestätigen [ 122 ]. In einer weiteren Studie von Lehmann et al.…”
Section: Befundungunclassified
“…The cardiac CTA should be evaluated and reported according to SCCT guidelines 68. This includes reporting of potential extracardiac findings and detection of additional or alternative potential causes of chest pain when excluding significant CAD 69…”
Section: Ct Perfusion For Detection Of Myocardial Ischemiamentioning
confidence: 99%
“…68 This includes reporting of potential extracardiac findings and detection of additional or alternative potential causes of chest pain when excluding significant CAD. 69 In addition to coronary evaluation, the cardiac CTA can be used for evaluation of myocardial attenuation at rest if no delayed acquisition is performed. 70 The presence of myocardial infarction should be evaluated using multiplanar reformat or minimum intensity projection with a slice thickness of 5 to 10 mm and a narrow window width and window level (eg, W 200, L 100 to 150 depending on mean myocardial attenuation).…”
Section: Cardiac Ctamentioning
confidence: 99%